THE USE OF COHERENCE ELEMENTS ON THE STUDENTS’ FORMATIVE TEST IN WRITING ANALYTICAL EXPOSITION TEXT OF ELEVENTH GRADE STUDENTS AT SMA SWASTA HANG KESTURI MEDAN - Rebecca Theresia Manullang; Isli Iriani Pane; Marisi Debora (Universitas Negeri Medan, 2021)
THE USE OF COHERENCE ELEMENTS ON THE STUDENTS’ FORMATIVETEST IN WRITING ANALYTICAL EXPOSITION TEXT OF ELEVENTHGRADE STUDENTS AT SMA SWASTA HANG KESTURI MEDAN*Rebecca Theresia Manullang** Dr.Isli Iriani Indiah Pane,S.Pd, M.Hum.** Marisi Debora, S.Pd, M.HumABSTRACTRebecca. Registration Number: 2153321029. The Use of Coherence Elementson The Students’ Formative Test in Writing Analytical Text of Eleventh GradeStudents at SMA Swasta Hang Kesturi Medan. A Thesis. English EducationStudy Program, Faculty of Languages and Arts, State University of Medan,2020.This research used quantitative research which aimed to evaluate the studentscoherence elements used in writing analytical exposition text. method throughdocumentation and interview.It was conducted in SMA Swasta HangKesturi,especially Eleventh Grade Students.The data consist of the existingEnglish Formative test items which were directly collected from English teacherand analyzed based on triangulation through documentation and interview. Thefindings implied that there were 4 coherencel elements according Oshima andHogue’s theory occurred in students formative test of SMA Swasta Hang KesturiMedan. They were transition signal 53%, Consistent Pronouns 40%, Repetition ofKeyword 2%, and Logical Order 5 %. Transition signal occurred in connecting;organize sentences and explaining the topic. Consistent pronouns occurred inreplacing and minimizing the use of the same word. Repetition of Keywordoccurred in remembering and understanding the topic of the text. Arrange the ideain logical order occurred based on experience and teachers’ outline.Furthermore,the students reason for selecting the elements are categorized to each elements.The students choose the transition signals to connect the sentences, explained thetopic, and organized the sentences. The reason in choosing the consistentpronouns is to replace or reduce the subjects, objects, names of people, things andso on. The reasons in choosing repetition of keywords is to remember about thetopic/issue that they are discussed in the essay. Additionally, the repetition ofkeyword helps the students to maintain the topic/ideas to keep in line withoutchanging anything. Furthermore, they need it to connect the topic in eachparagraph to the whole paragraph (essay).Keywords: Coherence, Writing,Analytical Exposition,Formative Test.